Character Education Implementation through Arabic Language Teaching within Indonesian National Curriculum 2013 Framework - Muhammad Nu'man (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2015)
Spiritual education is education related to spiritual or soul. Spiritual education in this paper has been defined as a concept of education system that emphasizes the development of spiritual capability or spiritual standards that can be perceived by learners to achieve the perfection of life according to Islamic standards. The development of spiritual capability is not limited to learners, but covers all educational actors. Spiritual education that meant by the author in this paper is a component within the competence contained in Curriculum 2013. The author describes in this paper about the application of spiritual education in learning Arabic based on curriculum 2013 and to know how the results of its application. The application of spiritual education in the Arabic language subjects taught by giving examples of sentences related to spiritual which customized to the theme of learning Arabic. Furthermore through habituation activities that can be implemented as an application of spiritual education such as performing dhuha prayer every morning, praying at each starting lessons, reading bismillah while doing something etc. The assessment results of the implementation of spiritual education in Arabic learning on Curriculum 2013 are very significant.